International financial information regulations and financial decisions in businesses - Janampa Gómez, Glady Guissela (2018)
The purpose of the research work is to facilitate financial decision making through the correct application of international financial reporting standards in companies. The research has been qualitative, descriptive and correlational in scope, non-experimental cross-sectional design, a population of 135 companies, the probabilistic sample has been 100 study subjects, the techniques used have been the survey and the documentary compilation, the data has been processed with the SPSS program. The following general conclusion was reached: The adoption of the International Financial Reporting Standards (IFRS) has a large impact on the financial decision making of companies; through the recognition of transactions, the measurement of transactions, the recording of transactions and the reasonable presentation of business transactions.